Little dragons prefer flowers to maidens: a lizard that laps nectar and pollinates trees - Sazima, Ivan; Sazima, Cristina [UNESP]; Sazima, Marlies (Instituto Virtual da Biodiversidade | BIOTA - FAPESP, 2005)
Lizards rarely visit and pollinate flowers, the few recent records being mostly restricted to island habitats. We report here on the Noronha skink (Euprepis atlanticus) seeking nectar in the flowers of the leguminous mulungu tree (Erythrina velutina) at Fernando de Noronha Archipelago, off northeast Brazil. The mulungu tree blooms during the dry season, and each flower secretes copious and diluted nectar throughout the day. The Noronha skink climbs up to the inflorescences and laps the nectar accumulated in the flowers' base. While exploiting the flowers and crawling over the inflorescences, the body parts of the skink contact the anthers and stigmas and pollen adheres to the lizard's scales. The lizard visits inflorescences from the same and different trees, which renders it a potential pollinator. As the mulungu tree blooms during the dry season and the island has little or no natural freshwater supply during drought periods, we suggest that the Noronha skink seeks flower nectar both for its energetic, diluted sugars and the water content.

Lagartos raramente visitam e polinizam flores, os poucos registros estando restritos a ambientes insulares. Registramos aqui a mabuia de Noronha (Euprepis atlanticus) buscando néctar nas flores da árvore leguminosa mulungu (Erythrina velutina), no Arquipélago de Fernando de Noronha ao largo da costa Nordeste do Brasil. O mulungu floresce na época seca, ao longo de quatro meses. As flores produzem néctar muito diluído e abundante, ao longo do dia todo. A mabuia percorre as inflorescências, lambendo o néctar acumulado na base da flor. Enquanto rasteja sobre as inflorescências da mesma ou outra árvore, contata as anteras e os estigmas e o pólen fica aderido ao seu corpo, o que torna a mabuia um polinizador potencial. Como o mulungu floresce durante a época seca, período em que a água é muito escassa na ilha, sugerimos que a mabuia visita as flores tanto pelos açúcares diluídos e energéticos, como pela água contida no néctar.
Keywords: Euprepis atlanticus; Scincidae; Erythrina velutina; Fabaceae; saurophily; oceanic islands; Euprepis atlanticus; Scincidae; Erythrina velutina; Fabaceae; saurofilia; ilhas oceânicas